SEX EDUCATION DALAM PEMBENTUKKAN KARAKTER ANAK PERSEKTIF PSIKOLOGI ISLAM - Assakinah, Nurul Fajri (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
Sex education is something that needs to be implemented in schools and in the family environment. For this research, qualitative research methods are used that emphasize values. Qualitative method is a research procedure that produces qualitative descriptive data in the form of words and in writing or verbally from the people and actors who are observed. This method is used to try to answer as a whole about Sex Education in the Character Building of Islamic Psychology Perspective Children, besides this research uses a qualitative descriptive method. This cannot be separated from the role of teachers at school and parents at home. Character formation is carried out by teaching children such as the Koran, playing educational games at school and in the family environment, teaching children to sing according to their abilities, teaching children to distinguish colors, good and bad traits when playing at school or at home and teaching children about organs. reproductions that can be seen and that cannot be seen that can be touched and that cannot be touched and improve the ability or train the mind not to think about pornographic things. Islamic psychology is present in the world of education in early childhood with a new paradigm, so that children not only understand the concept of life in general, but can understand the concept of human beings in Islam. So that children can be useful for family, community, religion, homeland and nation.